Child abuse and neglect - McCoy, Monica L. (Monica Louise); Keen, Stefanie M. (New York, NY : Psychology Press, 2014)
'Child abuse and neglect are examined in this new edition - the latest research, what it entails, and how to recognize and report it. Federal law mandates the reporting of suspected child maltreatment by many professionals. This book will appeal to those who one day find themselves in the role of a mandated reporter. The book opens with the background on child maltreatment including its history, an overview of the research, and the risk factors. Details about mandated reporting are also explored. Different forms of maltreatment - physical abuse, neglect, psychological maltreatment, sexual abuse, fetal abuse, and Munchausen by Proxy Syndrome--are then examined, along with the new chapter on resiliency. Incidence estimates and consequences for each type of maltreatment are provided. Legal issues including forensic interviewing are then reviewed. The book concludes with an example of what happens to a child after a report is filed along with suggestions for preventing child maltreatment. Intended as a text for courses in child abuse, child maltreatment, family violence, or sexual and intimate violence taught in psychology, human development, education, criminal justice, social work, sociology, women's studies, and nursing, this book is also an invaluable resource to workers who are mandated reporters of child maltreatment and/or anyone interested in the problem'--
Machine generated contents note: pt. I Introduction/Purpose -- ch. 1 Introduction -- A Brief History of Child Maltreatment -- Responding to Children in Crises -- Research on Maltreatment -- Conclusion -- Discussion Questions -- ch. 2 Risk Factors for Child Maltreatment -- Family Factors -- Child Factors -- Extrafamilial Factors -- Cultural Factors -- Conclusion -- Discussion Questions -- ch. 3 Mandated Reporting -- The History of Mandated Reporting -- Persons Required to Report -- When to Report -- How to Report -- Failure to Report -- Education Regarding Mandated Reporting -- Confidentiality and Mandated Reporting -- Is Mandated Reporting a Good Thing? -- Conclusion -- Discussion Questions -- pt. II Types of Abuse and Their Effects -- ch. 4 Physical Abuse -- Definition -- Prevalence and Incidence -- Corporal Punishment -- Consequences of Physical Abuse -- Caution: Not All Marks Are Signs of Abuse -- Marks From Folk Medicine Practices -- Nonphysical Consequences of Physical Abuse -- Conclusion -- Discussion Questions -- ch. 5 Child Neglect -- Definition -- Subtypes of Neglect -- Incidence -- Consequences of Neglect -- Intergenerational Transmission of Neglect -- Conclusion -- Discussion Questions -- ch. 6 Psychological Maltreatment -- Definition -- Defining a Line on a Continuum of Behavior -- Incidence -- Consequences of Psychological Maltreatment -- Conclusion -- Discussion Questions -- ch. 7 Sexual Abuse -- Definition -- Incidence and Prevalence -- Perpetrators -- Victims -- Extrafamilial Child Sexual Abuse -- Child Sexual Exploitation -- Consequences of Sexual Abuse -- Conclusion -- Discussion Questions -- ch. 8 Fetal Abuse -- Definition -- Incidence -- Causes of Fetal Abuse -- Effects of Drugs on Prenatal Development -- Responding to Fetal Abuse -- Conclusion -- Discussion Questions -- ch. 9 Munchausen by Proxy Syndrome -- Definition -- Victims -- Perpetrators -- Incidence -- Risk Factors -- Consequences of MPS -- Investigation of MPS -- Controversies Related to MPS -- Conclusion -- Discussion Questions -- ch. 10 Resilience -- Definition -- Conclusion -- Discussion Questions -- pt. III Legal Issues -- ch. 11 Forensic Interviewing of Child Victims -- Children Providing Testimony -- The Accuracy of Children's Testimony -- Recommendations for Conducing Good Forensic Interviews -- Conclusion -- Discussion Questions -- ch. 12 The Legal System and Child Maltreatment -- Children and the Courtroom -- Types of Courts -- Testifying in Court -- Conclusion -- Discussion Questions -- pt. IV What Happens Next -- ch. 13 The Maltreated Child and Child Protective Services' Response: What Happens After a Report Is Made? -- Intake and Screening -- Investigation and Initial Assessment -- Family Assessment -- Case Planning -- Service Provision -- Family Progress -- Case Closure -- Decision Making -- Conclusion -- Discussion Questions -- ch. 14 Preventing Child Maltreatment -- Overview of Prevention Programs -- A Public Health Issue -- Primary Prevention -- Secondary Prevention -- Conclusion -- Discussion Questions.
Dr.noor/klbf2014/love
Includes bibliographical references and index.
Keywords: Child abuse -- United States; Child abuse -- Law and legislation -- United States; PSYCHOLOGY / Developmental / Child; PSYCHOLOGY / Psychotherapy / Child & Adolescent; SOCIAL SCIENCE / Children's Studies; Etats-Unis.